If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -5)(5x + 2) = 0 Reorder the terms: x(-5 + 2x)(5x + 2) = 0 Reorder the terms: x(-5 + 2x)(2 + 5x) = 0 Multiply (-5 + 2x) * (2 + 5x) x(-5(2 + 5x) + 2x * (2 + 5x)) = 0 x((2 * -5 + 5x * -5) + 2x * (2 + 5x)) = 0 x((-10 + -25x) + 2x * (2 + 5x)) = 0 x(-10 + -25x + (2 * 2x + 5x * 2x)) = 0 x(-10 + -25x + (4x + 10x2)) = 0 Combine like terms: -25x + 4x = -21x x(-10 + -21x + 10x2) = 0 (-10 * x + -21x * x + 10x2 * x) = 0 (-10x + -21x2 + 10x3) = 0 Solving -10x + -21x2 + 10x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-10 + -21x + 10x2) = 0 Factor a trinomial. x((-2 + -5x)(5 + -2x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + -5x)' equal to zero and attempt to solve: Simplifying -2 + -5x = 0 Solving -2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 0 + 2 -5x = 0 + 2 Combine like terms: 0 + 2 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4Subproblem 3
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {0, -0.4, 2.5}
| x^2-10+25=4 | | 3+x=7x+-21 | | x^2*8=32 | | 16m+8=32 | | 7(-4-4x)=308 | | 6(6-15)+16+6= | | y^2+12y-45=0 | | (-7)(-5)+(-7)(-4)= | | ln(x)+ln(x+2)=8 | | 11=5*y-4 | | xy=15x^2 | | (2x-8)*(x+3)=0 | | 15=13+2x | | 5-2x=3-14x | | 16e-32=176 | | 9*b+5=23 | | 4(-4p+4)+6p= | | 7(-7x-1)=336 | | 1/2*?(x)=1 | | 2+7+X=6+3 | | 1.4-16(t+6)=4.6 | | (-3)(7)+(-3)(3)= | | 1/2?(x)=1 | | 3(2x+6)=0 | | 1/2?x=1 | | 50+.10t=10+.40t | | =(x^70)(sin*(8*x)) | | -10k-7(5-9k)= | | 7.2=-5x^2+12x | | -19k-7(5-9k)= | | 43s+.10=.40+30s | | =16(4) |